Políticas curriculares para formação de professores de química : a prática como componente curricular em questão - Lopes, Fabíula Torres Costa (2012)
This study lies in the field of current national policies for the training of teachers of Chemistry. The central goal is to analyze how Praxis as Curricular Component has been h w ’ g Ch y, fying the senses and directions involved in it. The courses are offered by the Federal University of Mato Grosso (UFMT), at its main campus, face-to-face mode, and by the Federal Institute of Mato Grosso (IFMT), in long-distance mode, as set in the context of the Open University of Brazil (UAB). The analysis was developed from the perspective that the conception of Praxis as Curricular Component articulates with the conception of politics that circulates in ampler contexts (of influence and text productions). This way, the theoretical contribution to the development of the analysis was based on authors who seek to devise educational policies as a cycle that involves various contexts and social actors, which implies recognizing that the State does not have absolute power over them. To begin with, policies are always subject to recontextualization, which is understood as a complex process of interpretation, decontextualization, resetting and refocusing of speeches that make such policies. With such intention, the methodology used for the developing the study was guided by: analyses of productions in the educational area of Chemistry, noting the purposes of the research, the conceptions of Praxis, and Praxis as a Curricular Component, the adopted theoretical referential, and the inherent problems to the subject; analyses of official texts that compose the national politics of formation of Chemistry teachers, observing the conceptions of Praxis as a Curricular Component, and defended demands; data-collecting on the description of the investigated courses, with special attention to the development of the subject of Educational Praxis, and the insertion of Praxis as Curricular Component; analyses of the Pedagogical Projects of the related courses; analyses of interviews with involved actors with Praxis as Curricular Component, with the intention to understand the senses and directions targeted to this component. The results of this study indicate that there are differences in the sense and direction attributed to Praxis as Curricular Component. In the design of the Chemistry course at UFMT, Praxis as Curricular Component is present since the beginning of the course and is regarded as a responsibility of all teachers. It is present in subjects of referred area and in specific subjects related to teachers' training. In the Chemistry course curriculum at IFMT/UAB, Praxis as Curricular Component appears directly linked to some subjects of didactic-pedagogic nature. It was concluded that there are different understandings attributed to Praxis as Curricular Component. The conditions, resources, histories and local commitments are different, fact that opens possibility of recontextualization, relocation and, consequently, of creation. Recontextualization can be explained as the combination of global and local logics, fact that produces, at the same time, identity and difference, homogeneity and heterogeneity, and refers to the conception of Praxis as Curricular Component as ''an v”.